Impact of human trafficking and domestic violence training on medical students’ preparedness to work with vulnerable populations - Rachel Geiser; Santana Solomon; Chase Irwin; Stacy Ruther; Kareem Raad (Cogent Education)
Healthcare workers have a unique opportunity to recognize and provide support to HT/DV victims. The objective of this study is to determine if students are more prepared to identify and work with these patient populations after being trained on the topic by the International Rescue Committee (IRC). The IRC came to the University of Arizona College of Medicine- Phoenix (UACOMP) to do an optional one hour training of HT/DV in healthcare for current first and second year medical students. After IRB approval from the UACOMP Research Office for Medical Education (ROME), pre and post surveys were given to a total of 26 students who attended the training. Wilcoxon Signed-Rank tests adjusted for multiple comparisons were used to evaluate differences between pre- and post-training scores. Students had statistically significant improvement in self-reported comfort level scores for recommending resources, providing care, and calling the national hotline for individuals who have experienced human trafficking and domestic violence. The marked improvement in students’ comfort providing resources and care to HT/DV victims after just a 1 h training from the IRC on these topics demonstrates the impact that early exposure to HT/DV education can have in vulnerable patient populations.